2014
DOI: 10.1371/journal.pone.0103008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-Alpha Induced by Hepatitis B Virus Core Mediating the Immune Response for Hepatitis B Viral Clearance in Mice Model

Abstract: Persistent hepatitis B viral (HBV) infection results in chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC). An efficient control of virus infections requires the coordinated actions of both innate and adaptive immune responses. In order to define the role of innate immunity effectors against HBV, viral clearance was studied in a panel of immunodeficient mouse strains by the hydrodynamic injection approach. Our results demonstrate that HBV viral clearance is not changed in IFN-α/β receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“…34 TNF-a has been described as potentially having a potentially modulating effect on HBV gene expression 35,36 and as being a key immune effector in HBV clearance in a study of a panel of immune effector-deficient mouse strains. 16,37 As an innate cytokine, TNF-a causes iMATE formation, which facilitates the expansion of the cytotoxic T-lymphocyte population against HBV. 31 Clinically, blockage of TNF-a with anti-TNF has been widely used in many immune-mediated diseases, including rheumatoid arthritis, ankylosing spondylitis, inflammatory bowel disease, psoriasis and psoriatic arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 TNF-a has been described as potentially having a potentially modulating effect on HBV gene expression 35,36 and as being a key immune effector in HBV clearance in a study of a panel of immune effector-deficient mouse strains. 16,37 As an innate cytokine, TNF-a causes iMATE formation, which facilitates the expansion of the cytotoxic T-lymphocyte population against HBV. 31 Clinically, blockage of TNF-a with anti-TNF has been widely used in many immune-mediated diseases, including rheumatoid arthritis, ankylosing spondylitis, inflammatory bowel disease, psoriasis and psoriatic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, studies from TNF-a knockout mice have also demonstrated that lack of the effect of TNF-a would impair the CD8 1 T-cell response to HBV, leading to ineffectiveness of viral clearance. 15,16 These observations indicate that TNF-a is a crucial innate cytokine for clearing HBV and eliminating HBV viral load in the host immune response against HBV infection.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…What is becoming clear is that immunosuppressive agents and particularly, biological agents, including anti-TNF therapy, can cause major flares in HBV-related disease, leading to morbidity and mortality (4,5). Animal models and particularly, immunocompetent mouse models of persistent HBV infection have been used to dissect host-pathogen interactions that influence infection outcomes (6)(7)(8). These animal models can be used to define host cell signaling and cell death pathways that contribute to the persistence or control of HBV infection.…”
mentioning
confidence: 99%